ANALISIS NILAI KARAKTER RELIGIUS DALAM NOVEL HATI SUHITA KARYA KHILMA ANIS - Dinda Zulaikhah; Rahmat (LP3M IAI Al Urwatul Wutsqo Jombang, 2021)
The character education in the 2013 curriculum is an effort to establish and improve the nation's character amid the phenomenon of moral degradation. Besides implanted directly during the learning process, character education also requires other efforts such as accompanied by interesting reading which contains the values of character education. This study focused on the values of character building, especially religious characters, which are the main character values in the Hati Suhita Novel by Khilma Anis.The purpose of this study was to analyze the values of character education and the religious characters contained in the Hati Suhita Novel more specifically. The writer used a qualitative approach by library study. The results showed Hati Suhita Novel contained 13 character values, namely: 1) Religious, 2) Hard work, 3) Creative, 4) Independent, 5) Democratic, 6) Curiosity, 7) Love their homelands, 8) Respect for achievement, 9) Friendly / communicative, 10) Love of peace, 11) Like to read, 12) Social care, and 13) Responsibility. The results also showed that religious characters in the novel were categorized into two types, namely 1) Divine value, which had 5 indicators, namely: trust, worship, gracefulness, surrender, steadfastness, and 2) Human value, which had 4 indicators, namely: cohesiveness, humility, true promises, maintaining self-respect and others.